Konsep Pendidikan Multikultural menurut Nadirsyah Hosen - Nurhasanah, Anah; Atoillah, Ahmad Nabil; Rohman, Ahmad Abdur (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2020)
Education is the most important factor in efforts to develop potential and knowledge and cultural values. In the context of a society that has diversity in various aspects ranging from religion, ethnicity, ethnicity to culture, it needs deep understanding as well as awareness of the importance of multicultural education to maintain togetherness and integrity of a nation. In an effort to realize these efforts, multicullural education is interpreted as a process of understanding the diversity that exists and the similarities to be able to respect each other. In order to realize an understanding of multiculturalism, it must be endeavored in the right way, namely through education. The focus of this research is (l) what is the concept of multicultural education according to Nadirsyah Hosen? (2) how is the relevance of Nadirsyah Hosen's multicultural education concept with the aim of Islamic education? In order to find answers to the above questions, the authors conducted research using a library research research approach or commonly referred to as literature review research. Sources of data obtained for this research library research can be in the form of research journals, dissertations, theses, theses, research reports, text books, papers, seminar reports, and / or official publications of the government or other institutions. The references are then processed using the content analysis method which aims to obtain the contents of the data and information then analyzed with a deductive thinking model, which departs from general theory to find applicative conclusions. The findings in this study are as follows: (l) The concept of multicultural education in Nadirsyah Hosen's view is to implement education that engages students who are not only intellectually intelligent but aware of national diversity. Providing equal opportunities to all students in obtaining education regardless of differences in racial, cultural, ethnic and religious backgrounds, in order to avoid discriminatory attitudes, fanaticism so as to form a tolerant attitude, respect for differences and culture. (2) Nadirsyah Hosen's thoughts regarding multicultural education are relevant to the goals of Islamic education. In Islam it is explained that the purpose of education is in accordance with the purpose of the creation of Allah's creatures. Becoming the unifier of the nation forms human beings who not only worship Allah or Ghair Mahdah but also respect the diversity of the nation which is known as mahdah worship. The relation with multicultural education is that religion has strong foundations in implementing education that understands a pluralistic nation